2014
DOI: 10.1139/cjp-2013-0670
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical calculation of the low-lying doublet electronic states of the SrF molecule

Abstract: The potential energy curves of the low-lying doublet electronic states in the representation 2s+1 ⌳ (+/−) of the SrF molecule have been investigated by using the complete active space self-consistent field with multireference configuration interaction and multireference Rayleigh-Schrödinger perturbation theory methods. The harmonic frequency, e ; the internuclear distance, R e ; the dipole moment; and the electronic energy with respect to the ground state, T e , have been calculated for the considered electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…The differences in the PDMs between the LERCCSD results in our earlier work and those in the present work for HgX were due to the choice of basis (DZ basis functions [8,57] in the former, as against a QZ basis in the current work). We observed that the values of PDM for SrF that were obtained by using the complete active space self-consistent field (CASSCF) approach to multi-reference CI (MRCI) and second-order Rayleigh-Schrodinger perturbation theory (RSPT2) [46] (which agreed with our nLERCCSD, as well as FFRCCSD results) underestimated and overestimated the results with respect to the experiment, respectively. The results for PDMs of SrF and BaF from Hao et al [48] using the exact two-component Hamiltonian-Fock space coupled-cluster (X2C-FSCC) formalism and the PDM of SrF from Sasmal et al [47] using a relativistic Z-vector coupled-cluster approach (with both works employing a QZ basis) agreed closely with the experimental values.…”
Section: Moleculesupporting
confidence: 85%
See 1 more Smart Citation
“…The differences in the PDMs between the LERCCSD results in our earlier work and those in the present work for HgX were due to the choice of basis (DZ basis functions [8,57] in the former, as against a QZ basis in the current work). We observed that the values of PDM for SrF that were obtained by using the complete active space self-consistent field (CASSCF) approach to multi-reference CI (MRCI) and second-order Rayleigh-Schrodinger perturbation theory (RSPT2) [46] (which agreed with our nLERCCSD, as well as FFRCCSD results) underestimated and overestimated the results with respect to the experiment, respectively. The results for PDMs of SrF and BaF from Hao et al [48] using the exact two-component Hamiltonian-Fock space coupled-cluster (X2C-FSCC) formalism and the PDM of SrF from Sasmal et al [47] using a relativistic Z-vector coupled-cluster approach (with both works employing a QZ basis) agreed closely with the experimental values.…”
Section: Moleculesupporting
confidence: 85%
“…SrF CASSCF-MRCI [46] 3.36 CASSCF-RSPT2 [46] 3.61 Z-vector [47] 3.45 LERCCSD [9,33] 3.6 2.17 FFCCSD [9] 3.62 2.16 X2C-MRCI [48] 3.20 X2C-FSCC [48] 3 2.96 LERCCSD [33] 3.4 6.50 FFCCSD [9] 3.41 6.46 X2C-MRCI [48] 2.90 X2C-FSCC [48] 3.23 Z-vector [50] 3.08 ECP-RASSCF [51] 7.5 RASCI [52] 7.28 MRCI [53] 5.1 MRCI [54] 6 Table 2. Individual correlation contributions to the effective electric fields (in GV/cm) of mercury monohalides (HgX; X = F, Cl, Br, and I), SrF, and BaF, from the LERCCSD (abbreviated as "L") and nLERCCSD (denoted by "nL") methods.…”
Section: Molecule Methods Pdm E Effmentioning
confidence: 99%
“…Heavier members of this series, particularly BaF and RaF, have been studied for the nuclear anapole moment [24][25][26][27], another parity-violating effect. The theoretical as well as experimental results of spectroscopic constants, valence properties and vibrational parameters for the ground -and excited states of AEMFs have also been reported by several research groups [26,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Nevertheless, there is a scope to carry out the calculations of P & T -odd interaction constants of these molecules consistently employing accurate many-body methods as there are only a very few calculations available in the literature.…”
Section: Introductionmentioning
confidence: 97%
“…A few theoretical studies of AEMF molecules that are being investigated in this work have already been reported in the literature. To mention: a detailed structural study of BaF molecule has been performed by Tohme and Korek [24]; the spectroscopy and evaluation of properties such as dipole moments of SrF molecules for the ground-and low -lying excited states has been performed by Jardali et al [25]; the electronic structure calculations for the ground-and several excited-states of XF (X = Be, Mg, Ca) molecules have been performed by Kork et al [26]. Further, the XF (X = Be, Mg, Ca, Sr, Ba) molecules together with mercury halides, and PbF have been studied by Abe et al [27] recently for the PDMs, and for effective electric fields (E ef f ) using relativistic finite -field coupled -cluster method with single and double excitations (FFCCSD).…”
Section: Introductionmentioning
confidence: 99%